THE TRACK RECORD OF USD STUDENT ORGANIZATIONS: A YOUNG DRIYARKARA CREATIVITY REVOLUTION - Brigida, Intan Printina (Sanata Dharma University, 2018)
This article describes the track record of student organizations (UKM) at Sanata Dharma University (SDU). This study tried to reveal the contribution of student organizations as a creativity revolution especially for students’ personality development, which will lead to the progress of SDU. The research type was a descriptive qualitative research which aims to elaborate the history of student organizations in SDU based on the viewpoint and spirit of youngDriyarkara. The method of the research were interviewing, gathering data, and analyzing results. The result of this study indicated that student organizations in SDU have contributed to improve students’ personality developments such as mental and physical development, cognitive and social development, public speaking and also vocal skill. Thus, the students are not only competent in hard skills but also soft skills which prioritize human values. DOI: https://doi.org/10.24071/ijhs.2018.010211